2015
DOI: 10.13189/nh.2015.030104
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Students' Learning in Student-dedicated Treatment Rooms during Clinical Nursing Education

Abstract: In the present study, a model which enables a combination of individual, formative assessment with summative assessment in a group was introduced and evaluated in clinical education. Based on a qualitative design, the study embodies research based on participation and theory founded on empirically practical try-outs. The one-year project included two Swedish universities and related health care settings within one hospital. Three groups participated in the study. A survey was conducted at the end of each perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Development of the new tool started with a literature review of current assessment tools. [6,7,9] The new assessment tool included course specific learning goals with assessment criteria. To support students' self-reflection and implementation of the learning goals the assessment tool included a question relating to the students' own strategies to reach their learning goals (see Figure 1).…”
Section: A New Assessment Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of the new tool started with a literature review of current assessment tools. [6,7,9] The new assessment tool included course specific learning goals with assessment criteria. To support students' self-reflection and implementation of the learning goals the assessment tool included a question relating to the students' own strategies to reach their learning goals (see Figure 1).…”
Section: A New Assessment Toolmentioning
confidence: 99%
“…Some universities have assessment tools that highlight the course-specific learning goals measuring whether intended learning outcomes have been reached or not. [6,7] Other studies have explored the assessment of competence within clinical practice, however, the focus has been on the intuitive aspects of assessing, in particular psychomotor abilities [8] rather than the multidimensional nature of competence such as nursing skills, knowledge and attitudes and values. [2] Another study on the development and validation of new tools measuring self-reported professional competence found that only a few tools for the assessment of nursing student competence tested the psychometric areas of competence.…”
Section: Introductionmentioning
confidence: 99%